Challenges of "Going Nano": Enhanced Electrochemical Performance of Cobalt Oxide Nanoparticles by Carbothermal Reduction and In Situ Carbon Coating. Issue 10 (10th April 2014) - Bresser, Dominic; Paillard, Elie; Niehoff, Philip; Krueger, Steffen; Mueller, Franziska; Winter, Martin; Passerini, Stefano
Abstract The electrochemical performance of nano‐ and micron‐sized Co3O4 is investigated, highlighting the substantial influence of the specific surface area on the obtainable specific capacities as well as the cycling stability. In fact, Co3O4 materials with a high surface area (i.e. a small particle size) show superior specific features, which are, however, accompanied by a rapid capacity fading, owing to the increased formation of an insulating polymeric surface film that results from transition‐metal‐catalyzed electrolyte decomposition. The simultaneous coating with carbon of Co3O4 nanoparticles and in situ reduction of the Co3O4 by a carbothermal route yields a CoOCoC nanocomposite. The formation of this material substantially enhances the long‐term cycling stability and coulombic efficiency of the lithium‐ion active material used. Although the metallic cobalt enhances the electronic conductivity within the electrode and remains electrochemically inactive (as revealed by in situ powder X‐ray diffraction analysis), it might have a detrimental effect on the long‐term cycling stability by catalytically inducing continuous electrolyte decomposition.